« Test de réalité » et limites du relativisme - Ivan Da Costa Marques (Revue d'anthropologie des connaissances)
I present an analytical framework of relations between science and power until the year 2008 around the food program MULTIMIXTURE, present in Brazil since the 1970s. I offer three ontologies, stories, or versions of reality. In each, the relationship between scientific knowledge about nutrition (institutionalized in academic laboratories and in the Federal Council of Nutritionists) and the program MULTIMIXTURE are transformed. I establish a hierarchy between the three versions of reality concerning their dialogic capacities. The first version of reality is determined by the analysis of biochemical components MULTIMIXTURE. The second is the version of reality on a “seamless tissue” of science and culture, nature and society, technical and political issues; it is a kind of version of reality brought into play by many studies in STS (Science and Technology Studies). The third is the version of reality enacted by an anthropologically informed history that escapes from the prison bounded by the “reality testing” dominant in Western culture.